Chile : Central Bank Transparency Code Review. (IMF Staff Country Reports; Country Report ;, 2021)
The Central Bank of Chile (CBC) has implemented broadly advanced transparency practices. This reflects the CBC's strong public commitment to transparency, which is anchored in the law and has been designated by the CBC as a strategic objective to fulfill its mandate. This policy has earned the CBC the broad trust of its stakeholders and has paid significant dividends for the CBC in terms of safeguarding its autonomy and ensuring its policy effectiveness.